Penataan Kawasan dan Penguatan Promosi Dalam Pengembangan Ekowisata Water Byur Ponjong - Septi Kurniawati Nurhadi; Atika Fatimah; Jeki Kuswanto; Dera Milyarta; Anita Kusumaning Tyas; Marcelinus Erix Nugroho; Muhammad Zakyul Fikri (Politeknik Negeri Cilacap, 2026)
Water Byur Ponjong is a water tourism destination in Gunung Kidul Regency, known for its swimming pools and various water rides, suitable for all ages. This area holds great potential, being divided into two main sites with distinct characteristics. However, its layout remains underdeveloped. The management has a strong desire to make Water Byur Ponjong a more organized, comfortable, and pleasant place to provide a tourism experience for every visitor. Unfortunately, several facilities have begun to deteriorate due to limited maintenance funds, necessitating support to maintain the area's sustainability. In response, mentoring activities were conducted to enhance the area's layout using an ecotourism approach and strengthen promotional strategies through the development of a tourism map and flyers. These efforts not only addressed the need for layout but also helped enhance the destination's image, making it more easily recognized and promoted. The entire series of activities resulted in three main outcomes: a regional master plan, a tourism map, and a tourism flyer. These three outcomes provide significant contributions to the development of Water Byur Ponjong ecotourism and open up opportunities to improve the quality of tourism services in the future.